Tuberculous meningitis at the Department of Child Health Dr. Pirngadi Hospital Medan (1979) - Sondang Tambunan; Adi Sutjipto; Rahayu Saat; A. J. Noeriman; Helena Siregar; Bistok Saing (Indonesian Pediatric Society, 1984)
A retrospective study on tuberculous meningitis had been carried out on 43 patients at the Department of Child Health, Dr. Pirngadi Hospital Medan during the year 1979. The peak incidence (55.81%) was found in the age group of less than 3 years of which 55.81% was in the second and 44,18% in the third stadium of the disease. Two of the cases were 4 months of age and 1 case was 14 years. None of the cases had got BCG immunization. Mortality rate was 37.21% of which 25% was in the second and 52.63% in the third stadium. Cerebrospinal fluid examination showed that 46.50% had cell counts between 101-500 cells/mm3. The symptoms were prolonged fever (62. 79%), convulsions (72.09%) and unconciousness (27.90%). Of these cases 83.72% had contact with tuberculous patients; 6.9% had positive tuberculin test and 48,83% showed pulmonary involvement on radiological examination. Nutritional status of these cases showed that 48.83% were undernourished and 34.82% were in poor nutritional status.